2012
DOI: 10.5491/shaw.2012.3.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Inhalation Toxicity Study of n-pentane in Rats

Abstract: ObjectivesThis study was conducted in order to obtain information concerning the health hazards that may result from a 13 week inhalation exposure of n-pentane in Sprague-Dawley rats.MethodsThis study was conducted in accordance with the Organization for Economic Co-operation and Development (OECD) guidelines for the testing of chemicals No. 413 'Subchronic inhalation toxicity: 90-day study (as revised in 2009)'. The rats were divided into 4 groups (10 male and 10 female rats in each group), and were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The overall no adverse effect level was the analytically determined concentration of 20483 mg/m 3 (approximately 7000 ppm), the highest concentration tested. These results were confirmed in a subsequent study (Kim et al 2012) in which similar exposure levels were tested and similar results were obtained with an overall no adverse effect concentration of 20300 mg/m 3 (approximately 6900 ppm).…”
Section: Repeated Dose Toxicitysupporting
confidence: 75%
See 3 more Smart Citations
“…The overall no adverse effect level was the analytically determined concentration of 20483 mg/m 3 (approximately 7000 ppm), the highest concentration tested. These results were confirmed in a subsequent study (Kim et al 2012) in which similar exposure levels were tested and similar results were obtained with an overall no adverse effect concentration of 20300 mg/m 3 (approximately 6900 ppm).…”
Section: Repeated Dose Toxicitysupporting
confidence: 75%
“…There are specific occupational exposure limits for n-hexane that are related to its neurological properties; for other aliphatic constituents of these solvents, occupational recommendations are set to avoid respiratory irritation and/or acute CNS effects. In repeated exposure studies, liver enlargement is commonly observed; male rat kidney effects associated with a2u-globulin induction are seen in studies of substances containing isoparaffinic and/or cycloparaffinic constituents, and small but statistically significant reductions in hematological parameters have been reported in some studies (Carrillo et al 2013, Carpenter et al 1975d, 1978, Galvin and Marashi 1999a, 1999b, 1999c, Kinkead et al 1985, Kim et al 2012, Malley et al 2000, Schreiner et al 1998, Sung et al 2010). As described above, liver enlargement without pathological changes or elevated levels of marker enzymes (ALT, AST) is considered to be an adaptive response rather than an adverse effect.…”
Section: Light Aliphatic Solvents (C5-c9)mentioning
confidence: 99%
See 2 more Smart Citations
“…Pentane excretion in breath has been previously used as an index of lipid peroxidation based on the premise that this hydrocarbon is not metabolized. However, it is now known that pentane is metabolized by the liver in animals into 2‐pentanol and that concentration of exhaled pentane is affected both by its production and by its metabolic loss…”
Section: Pentane In Exhaled Breath; Production By Lipid Peroxidationmentioning
confidence: 99%